A single amino acid switch converts the Sleeping Beauty transposase into an efficient unidirectional excisionase with utility in stem cell reprogramming. Issue 1 (28th November 2019) - Kesselring, Lisa; Miskey, Csaba; Zuliani, Cecilia; Querques, Irma; Kapitonov, Vladimir; Laukó, Andrea; Fehér, Anita; Palazzo, Antonio; Diem, Tanja; Lustig, Janna; Sebe, Attila; Wang, Yongming; et al.
Abstract: The Sleeping Beauty (SB) transposon is an advanced tool for genetic engineering and a useful model to investigate cut-and-paste DNA transposition in vertebrate cells. Here, we identify novel SB transposase mutants that display efficient and canonical excision but practically unmeasurable genomic re-integration. Based on phylogenetic analyses, we establish compensating amino acid replacements that fully rescue the integration defect of these mutants, suggesting epistasis between these amino acid residues. We further show that the transposons excised by the exc + /int − transposase mutants form extrachromosomal circles that cannot undergo a further round of transposition, thereby representing dead-end products of the excision reaction. Finally, we demonstrate the utility of the exc + /int − transposase in cassette removal for the generation of reprogramming factor-free induced pluripotent stem cells. Lack of genomic integration and formation of transposon circles following excision is reminiscent of signal sequence removal during V(D)J recombination, and implies that cut-and-paste DNA transposition can be converted to a unidirectional process by a single amino acid change.